2023
DOI: 10.1136/tsaco-2022-001056
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of non-steroidal anti-inflammatory drugs (NSAIDs) for the treatment of acute pain after orthopedic trauma: a practice management guideline from the Eastern Association for the Surgery of Trauma and the Orthopedic Trauma Association

Abstract: ObjectivesFracture is a common injury after a traumatic event. The efficacy and safety of non-steroidal anti-inflammatory drugs (NSAIDs) to treat acute pain related to fractures is not well established.MethodsClinically relevant questions were determined regarding NSAID use in the setting of trauma-induced fractures with clearly defined patient populations, interventions, comparisons and appropriately selected outcomes (PICO). These questions centered around efficacy (pain control, reduction in opioid use) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…The reviewer thoroughly assessed the methodological quality and risk of bias of the 15 included studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] using a modified ROBVIS tool (Figure 2). Overall, the studies were well conducted, with low risk of bias ratings across most domains.…”
Section: The Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The reviewer thoroughly assessed the methodological quality and risk of bias of the 15 included studies [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] using a modified ROBVIS tool (Figure 2). Overall, the studies were well conducted, with low risk of bias ratings across most domains.…”
Section: The Quality Assessmentmentioning
confidence: 99%
“…Outcome assessors were blinded in all the randomized trials, overcoming detection bias. Attrition and reporting bias were minimal, as most studies had complete outcome data and fully reported their pre-specified outcomes [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Overall judgments took these minor uncertainties into account, but the studies were still considered to have a reasonably low risk of bias.…”
Section: The Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Murphy et al demonstrated that NSAIDs reduce post-trauma pain and the need for opioid administration while having minimal risk of fracture nonunion. 9 Similarly, McDonald et al found that adding ketorolac to the postoperative drug regimen markedly decreased opioid consumption after the management of ankle fractures. 11 Nonetheless, there is a lack of literature on NSAID use as an opioid-sparing pain control regimen after IMN of closed tibial shaft fractures.…”
mentioning
confidence: 96%
“…7,8 In this context, NSAIDs present minimal risk to fracture healing and are a valuable option for perioperative pain control. 9 Furthermore, postoperative administration of NSAIDs leads to decreased opioid consumption and adequate pain control with few adverse effects in elective orthopaedic procedures. 10 Murphy et al demonstrated that NSAIDs reduce post-trauma pain and the need for opioid administration while having minimal risk of fracture nonunion.…”
mentioning
confidence: 99%